Issues in characterizing resting energy expenditure in obesity and after weight loss - Bosy-Westphal, Anja; Braun, Wiebke; Schautz, Britta; Müller, Manfred J. (Frontiers in Physiology, 2013)
Normalization of resting energy expenditure (REE) for body composition using the 2-compartment model (fat mass, FM and fat-free mass, FFM) has inherent limitations for the interpretation of REE and may lead to erroneous conclusions when comparing people with a wide range of adiposity as well as before and after substantial weight loss. We compared different methods of REE normalization: (i) for FFM and FM (ii) by the inclusion of %FM as a measure of adiposity and (iii) based on organ and tissue masses. Results were compared between healthy subjects with different degrees of adiposity as well as within subject before and after weight loss. Normalizing REE from an “REE vs. FFM and FM equation” that (i) was derived in obese participants and applied to lean people or (ii) was derived before weight loss and applied after weight loss leads to the erroneous conclusion of a lower metabolic rate (i) in lean persons and (ii) after weight loss. This is revealed by the normalization of REE for organ and tissue masses that was not significantly different between lean and obese or between baseline and after weight loss. There is evidence for an increasing specific metabolic rate of FFM with increasing %FM that could be explained by a higher contribution of liver, kidney and heart mass to FFM in obesity. Using “REE vs. FFM and FM equations” specific for different levels of adiposity (% fat mass) eliminated differences in REE before and after weight loss in women. In conclusion, the most established method for normalization of REE based on FFM and FM may lead to spurious conclusions about metabolic rate in obesity and the phenomenon of weight loss-associated adaptive thermogenesis. Using % fat mass-specific REE prediction from FFM and FM in kg may improve the normalization of REE when subjects with wide differences in % fat mass are investigated.